Literacy Using Food Truck Media in Writing Procedure Texts (Teaching Assistance Program in Educational Units) - Sisi Rosida; Rizky Vita Losi; Eka Surya Fitriani (Universitas Pendidikan Muhammadiyah (UNIMUDA) Sorong, 2023)
The teaching assistance program requires literacy learning activities carried out by students collaboratively with lecturers and teachers. The lack of students' ability to write procedural texts is due to a lack of familiarity with students' literacy activities that support their learning activities. This condition is seen from the students' lack of understanding in analyzing the general structure of the text, resulting in difficulties in creating procedural texts that are good and correct and can be utilized by readers. To overcome this problem, socialization was held which aimed to maximize writing procedural texts using Food Truck literacy media. This Community Service is located at Putra Anda Binjai Vocational School, where the Education Unit Teaching Assistance program is implemented. The methods used in this training are lectures, discussions and demonstrations. The results of the training show that food truck literacy learning can be used as an alternative in improving the ability to write procedural texts, this increases students' creativity in writing creative and useful procedural texts. During the activity, students played an active role in socializing fun learning literacy using Food Truck media